Optimasi Dosis Pupuk Kandang Ayam dan NPK pada Budidaya Kubis Bunga (Brassica oleracea var. Botrytis L.) - Irpan Gunawan; Atak Tauhid; Isna Tustiyani (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2021)
Cauliflower is one of the vegetables for consumers. The demand for cauliflower was rising so it must be scaled up with fertilizer. The purpose of this study was to study the effect of chicken manure and NPK fertilizer on the growth and yield of cauliflower. The study was conducted in Sukasenang Village, Banyuresmi Sub-district, Garut Regency from July to August 2019. The study used a Randomized Block Design (RBD) in two factors each of the 3 rates with 2 replications. The first factor was the rates of chicken manure which consisted of 0, 10 and 20 tons ha-1; the second factor was NPK fertilizer which consists of 0, 100 and 200 kg ha-1. The parameter of this research was plant height, number of leaves, leaf area, weight and diameter crud. The results showed that there was no interaction between the chicken manure and NPK fertilizer. The treatment of 20 tons ha-1 chicken manure affected the variable plant height, the number of leaves and leaf area. The rates of 200 kg ha-1 NPK fertilizer had affected plant height, number of leaves, weight and diameter crud.